Visualisasi Perempuan Dalam Film Wanita Tetap Wanita - Hudoyo, Sapto; Rachmawati, Irsa Richa (Capture : Jurnal Seni Media Rekam, 2014)
The main issues in the study that how the visualization of women in the movie  Wanita Tetap Wanita. This research used approach of qualitative descriptive especially the analysis study. The result that can be drawn in this study that the leadership spirit visualised by Medium Close-Up shots, meaning of the personal relationships showed by Medium Shot, the social relationships visualised in Full Shot, and the eye level camera indicates the level of fairness, equality or equal. Visualization of women who demonstrate leadership at a time when women are grappling with maintaining a job with patience and able to lead a family or can be called the backbone of the family. Visualization courage by taking close up pictures that have meaning or intimacy with the expression of someone’s reaction when they face the problem of women still smile and strong, brave women at the time of visualization to show her feelings to a man who already has a wife and children with movement of the Pan Right and Leftcamera show meaning of curiosity in atmosphere around. The results of the study showed that the movie  Wanita Tetap Wanita seeks to visualize the slick condition of women in fighting for their rights at each story according man’s perspective. Keywords :  women,  Wanita Tetap Wanita, and visualization